Design criteria for diagrid tall buildings: Stiffness versus strength. (11th November 2013) - Montuori, Giovanni Maria; Mele, Elena; Brandonisio, Giuseppe; De Luca, Antonello
SUMMARY The procedures and formulations suggested in literature for the design of diagrid structures start from the assumption that diagonal sizing process is governed by the stiffness requirements, as usually occurs for other, less efficient, structural types, and that member strength demand is automatically satisfied by the cross section resulting from the stiffness requirements. However, thanks to the high rigidity of the diagonalized façade, strength requirements can be of paramount importance and even be the governing design criterion. In this paper, stiffness and strength design criteria for diagrid structures are examined and translated in simplified formulae for quick member sizing. The application of the two approaches for the design of a 100‐storey building model, carried out for different diagrid geometrical patterns, gives the opportunity of discussing the relative influence of stiffness and strength on the design outcomes, in terms of resulting diagonal cross sections and steel weight, as well as on the structural performance. Copyright © 2013 John Wiley & Sons, Ltd.